Measurement of natural background radiation level in Darchula district, Nepal - Joshi, Prithivi Raj; Dhami, Akkal; Joshi, Bhawani Datt (Scientific World, 2022)
Natural background radiation level within Darchula district of Nepal was measured using a simple portable Geiger-Müller counter. Data were collected along six different directions at different places (three-five places) of the sample sites of the district and was averaged. The average data value with their standard deviation was used for analysis. In this study, the maximum radiation counts of 51.16 2.30 CPM were reported at Satan and the minimum counts of 25.96 2.30 CPM at Gokuleshwar. The observed radiation level of the Darchula district shows that the district is below the radiation risk level (nearly 100 CPM).